The benefits of Oukup to improve women sexual function after birth - Titi Nurhayati; Uyu Wahyudin; Iip Saripah; Joni Rahmat Pramudia (Eximia, 2024)
Oukup is a traditional spa that has been existing and developing for thousands of years on Batak Land including in Karo. The Karo tribe in North Sumatra practice oukup for tradional treatment for women health after child birth. Good body care will restore women health and its beauty as before the pregnancy and overcome sexual dysfunction. The purpose of this study was to determine the benefits of Oukup for women after giving birth. This research employed descriptive exploratory ethnomedicine research design with mixed methods. The subjects of this research were women who have given birth. In collecting the data this research used google form to see the characteristics of informants’ understanding of oukup and the benefits obtained of oukup, FSFI scores, interviews, and focus groups discussion to explore how to use adequate and perceived benefits while the analysis was processed through content analysis. The results of the study reveals that all respondents are of reproductive age. Some of the respondents had a score of 20-26.5 (50%) and those >26.5 were 26.5%, respondents experienced sexual dysfunction are 83.3%. The domains that had the highest scores were lubrication and satisfaction are 3.61 and pain in sexual intercourse. The use of oukup is felt for relaxation, treatment of insomnia, anemia and indirectly increases sexual arousal as after bathing, the body feels fresh, smells good and all impurities come out.hot aromatherapy steam can loosen blocked breathing. Thus, oukup is important tradional culture for improving women health, disease prevention.